Genome-wide identification and characterization of conserved and novel microRNAs in grass carp (Ctenopharyngodon idella) by deep sequencing. (June 2017) - Gong, Wangbao; Huang, Yong; Xie, Jun; Wang, Guangjun; Yu, Deguang; Sun, Xihong
Graphical abstract: Highlights: We identified 160 conserved miRNAs and 18 novel miRNAs in grass carp. Randomly selected 6 conserved and 2 novel miRNAs were confirmed their expression by stem-loop qRT-PCR assay. 1212 targets were predicted and these target genes were analysis by GO and results showed which are involved in many important biological processes. Abstract: MicroRNAs (miRNAs) are post-transcriptional regulators which bind to target to regulate protein expression by repressing translation or promoting degradation of the target mRNA. Studies have shown that deep sequencing is a powerful tool for the identification of miRNAs, and it is believed that may more miRNAs remain to be discovered in grass carp. In the present study, a pool of equal amounts of RNA obtained from 8 different adult grass carp tissues (spleen, liver, muscle, kidney, skin, testis, gut and heart) was sequenced using deep sequencing technology. A total of 16.579.334 raw reads were yielded from the pooled small RNA library. Using bioinformatics analysis, we identified 160 conserved miRNAs and 18 novel miRNAs in grass carp. Randomly selected 6 conserved and 2 novel miRNAs were confirmed their expression by stem-loop qRT-PCR assay. Furthermore, the 1212 potential targets of these miRNAs were predicted using miRNA target prediction tool. GO and KEGG pathway enrichment analyses indicated relevant biological processes. Our study provides the first genome-wide investigation of miRNAs from 8 mixed tissues of grass carp, and the data obtained expand the known grass carp miRNA inventory and provide a basis for further understanding functions of grass carp miRNAs.